2020
DOI: 10.1123/ijspp.2019-0185
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Quality’s Association With Soccer Injuries: Preliminary Data

Abstract: Purpose: To investigate the relationship between sleep quality and quantity and injuries in elite soccer players and to compare sleep–wake variables and injury characteristics. Methods: The current investigation was a prospective cohort study of 23 elite male soccer players competing for 2 teams over 6 mo in the highest-level Brazilian competition. The players’ sleep behavior was monitored for 10 d in the preseason using self-reporting sleep diaries and wrist activity monitors to determine sleep duration and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 30 publications
2
33
0
1
Order By: Relevance
“…Sleep might be associated with the risk for injury and illness [ 2 ]. Studies have found that soccer players with shorter sleep duration and with low-quality (nonrestorative) sleep showed increased numbers and severities of musculoskeletal injuries [ 17 , 18 ]. In addition, Laux et al [ 19 ] found that subjective sleep quality was associated with injury occurrence among elite soccer players in the month following an assessment, highlighting the role of sleep quality in the recovery process.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep might be associated with the risk for injury and illness [ 2 ]. Studies have found that soccer players with shorter sleep duration and with low-quality (nonrestorative) sleep showed increased numbers and severities of musculoskeletal injuries [ 17 , 18 ]. In addition, Laux et al [ 19 ] found that subjective sleep quality was associated with injury occurrence among elite soccer players in the month following an assessment, highlighting the role of sleep quality in the recovery process.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is not unreasonable to propose that some discrepancies in our training profiles may illustrate different training load demands among players' health status and playing positions [6,[9][10][11], as coaches regularly implement training drills that arrange the players according to their condition and match duties. Factors in addition to training load are likely to inhibit players' performance [17,18,21,22]. In this context, sports science literature suggests that higher sleep quality and proper fitness wellbeing may enhance players' physical and technical performance, while sleep disturbance, muscular soreness, and fatigue accumulation have been associated with performance impairment and higher musculoskeletal injury risk [17,18,21,22].…”
Section: Plos Onementioning
confidence: 99%
“…Factors in addition to training load are likely to inhibit players' performance [17,18,21,22]. In this context, sports science literature suggests that higher sleep quality and proper fitness wellbeing may enhance players' physical and technical performance, while sleep disturbance, muscular soreness, and fatigue accumulation have been associated with performance impairment and higher musculoskeletal injury risk [17,18,21,22]. Nevertheless, this study found an improbable relationship between players' wellness markers and training responses (i.e., despite cluster LOW exposed higher symptoms of muscular soreness, fatigue, and stress, [31].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations